5-7(2x-3(x-4))=6(2x-3)-4

Simple and best practice solution for 5-7(2x-3(x-4))=6(2x-3)-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-7(2x-3(x-4))=6(2x-3)-4 equation:


Simplifying
5 + -7(2x + -3(x + -4)) = 6(2x + -3) + -4

Reorder the terms:
5 + -7(2x + -3(-4 + x)) = 6(2x + -3) + -4
5 + -7(2x + (-4 * -3 + x * -3)) = 6(2x + -3) + -4
5 + -7(2x + (12 + -3x)) = 6(2x + -3) + -4

Reorder the terms:
5 + -7(12 + 2x + -3x) = 6(2x + -3) + -4

Combine like terms: 2x + -3x = -1x
5 + -7(12 + -1x) = 6(2x + -3) + -4
5 + (12 * -7 + -1x * -7) = 6(2x + -3) + -4
5 + (-84 + 7x) = 6(2x + -3) + -4

Combine like terms: 5 + -84 = -79
-79 + 7x = 6(2x + -3) + -4

Reorder the terms:
-79 + 7x = 6(-3 + 2x) + -4
-79 + 7x = (-3 * 6 + 2x * 6) + -4
-79 + 7x = (-18 + 12x) + -4

Reorder the terms:
-79 + 7x = -18 + -4 + 12x

Combine like terms: -18 + -4 = -22
-79 + 7x = -22 + 12x

Solving
-79 + 7x = -22 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
-79 + 7x + -12x = -22 + 12x + -12x

Combine like terms: 7x + -12x = -5x
-79 + -5x = -22 + 12x + -12x

Combine like terms: 12x + -12x = 0
-79 + -5x = -22 + 0
-79 + -5x = -22

Add '79' to each side of the equation.
-79 + 79 + -5x = -22 + 79

Combine like terms: -79 + 79 = 0
0 + -5x = -22 + 79
-5x = -22 + 79

Combine like terms: -22 + 79 = 57
-5x = 57

Divide each side by '-5'.
x = -11.4

Simplifying
x = -11.4

See similar equations:

| 5x+1/2-x-3/3=4 | | 9x-15=6x+14 | | -3(x-5)=-9 | | U/16=v | | 384=2x-170 | | x+1=-2x-23 | | 6(u-4)=18 | | x^4+5x^2-6x^3-30x=0 | | -y+12=11-4y | | 6(x+3)-10=23 | | 2(2v+7)=46 | | (3/x)+(7/x-6) | | x^2+196=28x | | 5x/2+10=15 | | 7x=18+5x | | 7(c-4)+6=5+c-27 | | 6t-22=14 | | -4(x-3)=2x | | x+3=5x+27 | | 1x-=9+x | | 6x-2=14x+2 | | V-5/6=-1/5 | | 16+7d=37 | | 8a^2-2=0 | | (x^2+2x+6)(2x^2-4x-1)= | | 8t-19+t=35 | | 19=h/8+14 | | 2x^3-3x^2+9x+2=-2 | | C+10+c=18 | | 4x-6=x+24 | | x^3+2=x-3 | | s/9+60=68 |

Equations solver categories